DETERMINATION OF AMINO ACIDS IN ERIOBOTRYA JAPONICA SEED BY HPLC (Scientific journal of the Fergana State University, 2024)
Amino acids are involved in the synthesis of proteins, enzymes, nucleic acids, fats and hormones, forming physiologically important compounds. Since they have a wide pharmacological spectrum of action, they are easily absorbed by the body, and also serve as a safe remedy for the human body. The widespread use of plants with essential amino acids in folk medicine, the manufacture of safe medicines is one of the most pressing issues today. The aim of the study was to study the amino acid composition of the seeds of the fruits of the lotiobotrya Japonica plant by qualitative and quantitative high-performance liquid chromatography. The seeds of the eriobotrya Japonica fruit grown in the Ferghana region were selected as a sample, the amino acids in which were detected using the fluorescence detector (FLD) of the Agilent 1260 II Infiniti HPLC device. 18 different amino acids were qualitatively and quantitatively analyzed in the sample. According to the results obtained, it was found that there are 13 types of amino acids, with the largest amount of lysine (18.947 mg/g) present. Arginine (0.0656 mg/g), valine (0.0474 mg/g), histidine (0.0144 mg/g), isoleucine (0.16 mg/g), methionine (0.017 mg/g), tryptophan (0.097 mg/g), phenylalanine (0.0425 mg The amino acids glycine (0.927 mg/g), alanine (0.207 mg/g), Serine (0.2839 mg/g) and tyrosine (0.034 mg/g) were studied from substituted amino acids. According to the results obtained, it was found that the sample contains 13 types of amino acids, with the largest amount of lysine (18.947 mg/g). Arginine (0.0656 mg/g), valine (0.0474 mg/g), histidine (0.0144 mg/g), isoleucine (0.16 mg/g), methionine (0.017 mg/g), tryptophan (0.097 mg/g), phenylalanine (0.0425 mg The amino acids glycine (0.927 mg/g), alanine (0.207 mg/g), Serine (0.2839 mg/g) and tyrosine (0.034 mg/g) were studied from substituted amino acids. The amount of essential amino acids ranged from 0.0144 mg/g to 18.947 mg/ g. The seeds did not contain the amino acids leucine, glutamine, asparagine, proline and trianine. The presence of essential amino acids in the composition of Eriobotrya Japonica seeds, along with other biologically active compounds, indicates its therapeutic value, and also lays the foundation for the development of new types of natural remedies.